Indonesian social policy development in a context of global social governance - Alexandra Kaasch; Mulyadi Sumarto; Brooke Wilmsen (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper reports the ideational and expertise roles and positions of global social policy actors. A particular emphasis is on the role of international organizations in supporting social policy development in Indonesia. These agencies include the World Bank, ILO, WHO, UNDP, UNICEF and FAO. It engages with the following key questions: which external policy actors have engaged in social policy issues in Indonesia? What were their perspectives, ideas, preferences or requests? And, how has their role changed as the country has developed? Analytically, it employs a global social policy and governance perspective, and focus on social policy prescriptions of global policy actors. This paper discusses several international organizations represented in Indonesia, their collaborative activities and their "ideas" of Indonesian social policy development.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives from and for the Global South
Keywords: 330